Adequate: rewriting the logics of success in rhetoric and composition - Oleksiak, Timothy, editor; Barsczewski, Joshua, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2026)
Adequate: Rewriting the Logics of Success in Rhetoric and Composition proposes a fresh approach to teaching rhetoric and composition-a field awash with unrealistic labor expectations and untenable and often unattainable requirements for both the educator and the educated-that takes "success" and "failure" out of the equation and advocates for the concept of adequacy over that of perfection. Fourteen essays from established scholars, ranging from deeply personal, to darkly humorous, to impassioned and blunt, offer theoretical and pragmatic resources for responding to unjust labor extraction and the discipline's demands that teachers do it all. Drawing on an array of intellectual traditions including labor studies, feminist rhetoric, disability studies, Jewish rhetoric, and theories of writing program administrations, authors assert the reasonable position of being enough and thriving outside of work in the face of growing demands for professional excellence and even perfection. Adequate reimagines what the concept of adequacy holds for the future of academic work. An invaluable resource for scholars, graduate students, and advanced undergraduate students in the rhetoric and composition field, this volume covers the realities of teaching rhetoric and composition in the modern college environment, as well as potential paths forward for educators in need of a better work-life balance.--Provided by publisher.
Introduction: Considering the work of adequacy in rhetoric and rhetoric and composition / Timothy Oleksiak and Joshua Barsczewski -- Solidarity as "living": a theory of relationality for community building as women of color in academia / Eunjeong Lee, Sara P. Lopez Amezquita, and Amy Wan -- Imagining a critical, coalitional kindness: moving beyond niceness to envision a discipline of care and cooperative disagreement / Mara Lee Grayson -- Rhetorical theory and the fight for a living wage / Olivia Wood -- An honest job application / Katie Manthey -- A dialogue on un/learning institutional knowledge in bits and doing the work as pre-tenure administrators / Kelin Loe, Ashanka Kumari, and Gavin P. Johnson -- Embodying (in)adequacy: "good enough" as a blow against the meritocratic regime / Christina V. Cedillo, Vyshali Manivannan, Ada Hubrig, and Bernice Olivas -- Temporarily adequate: learning to be enough at the writing center / Lauren Silber, Malaika Fernandes, Tenzin Jamdol, Audrey Auerbach Nelson, Xiran Tan, and Shaouxuan Tian -- A labor of love: a generational conversation about success, living well, and all that / Jen Wingard and Rachelle A. C. Joplin -- Overachieving to leave: reflections on an early career in transition / Sara Doan -- Confrontations in adequacy in pandemic teacher training / Crystal Colombini, Stephanie Kerschbaum, and Sara Webb-Sunderhaus -- Laboring through the life cycle: toward a disciplinary approach to faculty evaluation / Laurie A. Pinkert and Lauren Marshall Bowen -- This is fine: reflecting on (missed) opportunity and adequate moments of departmental collaboration, labor, and care / Brigitte Mussack -- We will never be enough (because academia will always demand more): a letter from a fledgling "crip doula" / Ada Hubrig -- Afterword: Maturing and organizing towards/with/for adequacy / Seth Kahn and Tony Scott.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Educational productivity; Educational accountability